Direct N(2)H(4)/H(2)O(2) Fuel Cells Powered by Nanoporous Gold Leaves - Yan, Xiuling (Nature Publishing Group, 2012)
Dealloyed nanoporous gold leaves (NPGLs) are found to exhibit high electrocatalytic properties toward both hydrazine (N(2)H(4)) oxidation and hydrogen peroxide (H(2)O(2)) reduction. This observation allows the implementation of a direct hydrazine-hydrogen peroxide fuel cell (DHHPFC) based on these novel porous membrane catalysts. The effects of fuel and oxidizer flow rate, concentration and cell temperature on the performance of DHHPFC are systematically investigated. With a loading of ~0.1 mg cm(−2) Au on each side, an open circuit voltage (OCV) of 1.2 V is obtained at 80°C with a maximum power density 195 mW cm(−2), which is 22 times higher than that of commercial Pt/C electrocatalyst at the same noble metal loading. NPGLs thus hold great potential as effective and stable electrocatalysts for DHHPFCs.